ZAMONAVIY TA’LIMDA MATEMATIKANI AMALIYOTGA YO‘NALTIRIB O‘QITISH - Gafforova Sarvinoz (Innovate Conferences, 2025)
This article explores the significance of practice-oriented approaches in modern mathematics education. It analyzes how connecting mathematical concepts with practical activities, real-world tasks, and interdisciplinary applications enhances students’ motivation and understanding. The paper highlights strategies such as contextualized learning, mathematical modeling, project-based learning, and the use of digital tools to develop students’ critical thinking and problem-solving skills. Practical recommendations are provided for teachers to incorporate life-based examples, financial calculations, measurement activities, and data analysis into mathematics lessons.
Keywords: practice-oriented learning, mathematics education, real-world applications, modeling, project-based learning, motivation.